Potensi Dan Prospek Pemanfaatan Rusa Timor Di Indonesia - Sri Murni Soenarno (IJEEM - Indonesian Journal of Environmental Education and Management, 2023)
Rusa deer or Cervus timorensis or Rusa timorensis is an Indonesian endemic tropical deer. This species is protected by Indonesian regulations. Rusa deer are protected because the population is already scarce. This article was a literature review about one of the efforts to increase the population by captivity. Deer captive breeding is a form of sustainable use of deer as well as conservation to prevent the extinction of deer animals. The success of deer captive breeding efforts is supported by mastery of knowledge about deer biology and captive management. The deer captive breeding program will be supported by many parties if it can provide meat to meet the food needs of the community.